Implementation of Religious Moderation Values in Scouting Extracurricular Activities - Muhammad Pazri Nasrullah; Asmawati Asmawati; Sondra Swestyani (STAI Serdang Lubuk Pakam, 2025)
Strengthening religious moderation in educational environments is an urgent need amid rising cases of intolerance among students. Lahei 1 Public High School, as a multicultural school, provides a strategic space to examine how Scouting extracurricular activities function as a means of shaping moderate character. This study aims to describe the implementation of religious moderation values in Scouting activities, identify the values applied, and analyze their influence on student character. The research method used is descriptive qualitative through observation, interviews, and documentation, while data validity is strengthened by triangulation of sources and techniques. The results of the study show that Scouting activities are an effective medium for internalizing religious moderation values, especially tolerance, anti-violence, national commitment, and accommodation of local culture. These values are evident in interfaith cooperation, peaceful conflict resolution, discipline, spirit of nationalism, and integration of local culture in Scouting activities. The implementation of these values of moderation has a positive impact on students' character, making them tolerant, empathetic, and able to live harmoniously amid diversity. These findings imply that Scouting activities can be a model for strengthening religious moderation in multicultural schools.